An analysis of thermal performance and entropy generation in a wavy enclosure with moving walls - Chattopadhyay, Anirban; Pandit, Swapan K.; Öztop, Hakan Fehmi (Elsevier, 2020)
This study presents an analysis of thermal performance in a both sided wavy enclosure with various moving walls. The plane walls of the enclosure are allowed to move in its own plane at a constant speed. Furthermore, one of the plane walls is heated nonuniformly while all other walls are maintained at constant cold temperature. The governing Navier-Stokes (N-S) equations in streamfunction-vorticity (psi - zeta) form coupled with the energy equation representing incompressible viscous flows are solved using our recently proposed fourth order compact scheme on nonuniform curvilinear grids (Pandit and Chattopadhyay, 2017). In order to observe the effects of the pertinent dimensionless parameters such as Richardson number (0.01 <= Ri <= 100), Grashof number (Gr = 10(4)), the wavy surface amplitude (0 <= lambda <= 0.06), and number of undulations (0 <= d <= 2) along the wavy surfaces on the fluid flow and the thermal performance of the cavity, the streamlines, isotherms contours and Nusselt numbers are studied. We have carried out nine cases (Case-1 to Case-9) for moving both the plane walls depending on the direction of moving walls and inclination angles. The issues of entropy generation are also analyzed based on the obtained dimensionless velocity and temperature values. (C) 2019 Elsevier Masson SAS. All rights reserved.
Keywords: Mixed convection; Wavy surface; Lid driven cavity; Compact scheme; Entropy generation